2010
DOI: 10.1159/000314543
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Primary Systemic Vasculitis with the Inosine Monophosphate Dehydrogenase Inhibitor Mycophenolic Acid

Abstract: Despite advances in the treatment of vasculitis, modern therapies fail to induce or maintain remission in a significant proportion of patients. Mycophenolic acid is increasingly used to treat vasculitis syndromes. Here, we consider relevant pharmacokinetic and pharmacodynamic properties of mycophenolate, with emphasis on the impact of renal impairment, and we review the existing evidence for and current trials of mycophenolate in the treatment of primary systemic vasculitides.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 141 publications
0
6
0
Order By: Relevance
“…Different case studies demonstrate reasonable efficacy of MMF in inducing remission in patients with AAV (reviewed in [51]). Its active metabolite mycophenolic acid suppresses guanine synthesis in lymphocytes by inhibiting inosine monophosphate dehydrogenase, and blocks DNA synthesis and proliferation after activation.…”
Section: Mycophenolate Mofetilmentioning
confidence: 99%
“…Different case studies demonstrate reasonable efficacy of MMF in inducing remission in patients with AAV (reviewed in [51]). Its active metabolite mycophenolic acid suppresses guanine synthesis in lymphocytes by inhibiting inosine monophosphate dehydrogenase, and blocks DNA synthesis and proliferation after activation.…”
Section: Mycophenolate Mofetilmentioning
confidence: 99%
“…Mycophenolic acid (MPA), the active form of mycophenolate mofetil (MMF), is an immunosuppressant increasingly used for remission maintenance after induction therapy for systemic lupus erythematosus (SLE) and antineutrophil cytoplasmic antibody-associated vasculitides (AAV) 1,2 . However, no recommendations concerning optimal dose of MMF for AAV are available, and a high relapse rate might compromise its use as a first-line remission-maintenance therapy 3 .…”
Section: To the Editormentioning
confidence: 99%
“…As maintenance therapy, the MAINTAIN study showed that MMF is as effective as azathioprine . For vasculitis, a group of disorders due to an inflammation of blood vessels, MMF has also demonstrated efficacy . MPA pharmacokinetics (PK) are complex and have been extensively studied in renal transplant recipients.…”
Section: Introductionmentioning
confidence: 99%